Continuous Transfer Hydrogenation of Sugars to Alditols with Bioderived Donors over Cu–Ni–Al Catalysts. Issue 10 (18th May 2015) - Scholz, David; Aellig, Christof; Mondelli, Cecilia; Pérez‐Ramírez, Javier
Abstract The front cover artwork for Issue 10/2015 is provided by the group of Prof. Javier Pérez‐Ramírez at the ETH Zurich. The cover depicts the give‐and‐take concept at the heart of an emerging continuous transfer hydrogenation process for the conversion of sugars to alditols. See the Full Paper itself at http://dx.doi.org/10.1002/cctc.201403005.